2015
DOI: 10.1186/s12884-015-0506-3
|View full text |Cite
|
Sign up to set email alerts
|

“My midwife said that having a glass of red wine was actually better for the baby”: a focus group study of women and their partner’s knowledge and experiences relating to alcohol consumption in pregnancy

Abstract: BackgroundWhile it is well established that alcohol can cross the placenta to the foetus and can affect an infant’s development, many women continue to drink during pregnancy. For this reason it is important to determine what information is being provided, what information may be missing, and the preferred sources of information on this issue. In order to improve prevention strategies, we sought to understand the knowledge and experiences of pregnant women and their partners regarding the effects of alcohol co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(94 citation statements)
references
References 20 publications
9
82
2
1
Order By: Relevance
“…Other studies in the Netherlands have estimated any alcohol consumption during pregnancy to be about 20% and 50% (Advies Stuurgroep Zwangerschap en Geboorte (Advisory Committee on Pregnancy and Childbirth), Dec 2009; Lanting et al, 2015). It may be that too few opportunities for alcohol consumption had occurred by the time the visit took place in our study (median 8 weeks), but women may also have under-reported their alcohol consumption, as has been reported in other studies (Crawford-Williams et al, 2015;van der Wulp et al, 2013). This advocates explaining possible risks of even small amounts of alcohol to all pregnant women.…”
Section: Association With Client Characteristicssupporting
confidence: 51%
“…Other studies in the Netherlands have estimated any alcohol consumption during pregnancy to be about 20% and 50% (Advies Stuurgroep Zwangerschap en Geboorte (Advisory Committee on Pregnancy and Childbirth), Dec 2009; Lanting et al, 2015). It may be that too few opportunities for alcohol consumption had occurred by the time the visit took place in our study (median 8 weeks), but women may also have under-reported their alcohol consumption, as has been reported in other studies (Crawford-Williams et al, 2015;van der Wulp et al, 2013). This advocates explaining possible risks of even small amounts of alcohol to all pregnant women.…”
Section: Association With Client Characteristicssupporting
confidence: 51%
“…First, health professionals should be aware that all women, including those who subscribe to the recommendation of abstinence and choose to abstain, can face difficulties that are not necessarily disclosed to them. As argued by prior research , the practitioner′s ability to initiate an open and non‐judgmental discussion with women about their alcohol consumption habits is essential to provide adequate support, especially to those with substance use issues . Second, our findings encourage health professionals to view pregnancy as a complex transition.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, health professionals’ ability to effectively prevent FASD in an all‐of‐community way may be hindered by gaps in resources designed specifically for men, grandmothers and aunties. Previous studies have highlighted the important role that men, grandmothers and aunties have in influencing Indigenous Australian women's decisions to consume alcohol during pregnancy . These social networks have the potential to become vital community advocates if they are effectively educated and supported in their role to prevent FASD .…”
Section: Discussionmentioning
confidence: 99%
“…Many Australian women are unaware of the potential harm caused by drinking alcohol during pregnancy and the potential risk of FASD. In 2013, a national study found that one in four Australian women continued to drink after learning they were pregnant and only 53% abstained from alcohol during their entire pregnancy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation